Grow proof ability student through mathematical working space strategies - Isnani, Isnani; Waluya, S.B.; Dwijanto, Dwijanto; Asih, T.S.N. (Edelweiss Applied Science and Technology, 2025)
This research aims to assist students in solving mathematical proof problems. This qualitative study investigates the proving ability of mathematics education students in the Real Analysis course, with a special focus on sequence material. The research design incorporates experiments to evaluate the effectiveness of the strategies used. Participants are students who take part in the Real Analysis program at private universities in the northern coastal region of western Central Java, Indonesia, specifically in Tegal City during the 2022/2023 academic year. Three study participants were selected, each representing a different level of evidentiary ability. Data is collected through work documents, interviews, and structured testing, and then analyzed using iterative techniques, including data condensation, data exposure, and verification. The findings show that most students can follow the evidence and correct their mistakes. In the future, this research will prioritize developments related to proof to improve quality-proof capabilities and explore the obstacles faced in studying proof problems. This research can ultimately contribute to more effective teaching of Real Analysis by providing a deeper understanding of the evidence problem that can be easily learned.